vzorce : (a+b)2 ; (a-b)2 ; a2 – b2 (a + b)2 = a2 + 2ab + b2 = (a+b).(a+b) (a - b)2 = a2 - 2ab + b2 = (a-b).(a-b) a2 - b2 = (a + b) . (a – b) 1. Rozložte na súčin podľa vzorca : a2 – b2 t2 – 100 = __________________________________________________________ 2. Rozložte na súčin: a) 4x2 + 20xy + 25y2 = __________________________________________________ b) 4x2 – 12x + 9 = _____________________________________________________ 2. Rozložte na súčin podľa vzorca: (a+b)2 a) 25x2 + 10xy + y2 = __________________________________________________ b)a2 + 4ab + 4b2 =____________________________________________________ c) 4m2 + 12mn + 9n2 =__________________________________________________ d) 16x2 + 24xy + -y2 = __________________________________________________ e) 9a2 + 6ab + b2 =_____________________________________________________ 3. Rozložte na súčin pomocou vzorca: (a - b)2 a) a2 – 4a + 4 = ________________________________________________ b) x2 – 2x + 1 =_________________________________________________ 4. Rozložte na súčin použitím vzorca a2 – b2 a) x2 – 100y2 =_________________________________________________ b) 25m2 – n2 =_________________________________________________ c) a2 – 25b2 =_________________________________________________ vzorce : (a+b)2 ; (a-b)2 ; a2 – b2 (a + b)2 = a2 + 2ab + b2 = (a+b).(a+b) (a - b)2 = a2 - 2ab + b2 = (a-b).(a-b) a2 - b2 = (a + b) . (a – b) vzorce : (a+b)2 ; (a-b)2 ; a2 – b2 (a + b)2 = a2 + 2ab + b2 = (a+b).(a+b) (a - b)2 = a2 - 2ab + b2 = (a-b).(a-b) a2 - b2 = (a + b) . (a – b) vzorce : (a+b)2 ; (a-b)2 ; a2 – b2 (a + b)2 = a2 + 2ab + b2 = (a+b).(a+b) (a - b)2 = a2 - 2ab + b2 = (a-b).(a-b) a2 - b2 = (a + b) . (a – b) vzorce : (a+b)2 ; (a-b)2 ; a2 – b2 (a + b)2 = a2 + 2ab + b2 = (a+b).(a+b) (a - b)2 = a2 - 2ab + b2 = (a-b).(a-b) a2 - b2 = (a + b) . (a – b) vzorce : (a+b)2 ; (a-b)2 ; a2 – b2 (a + b)2 = a2 + 2ab + b2 = (a+b).(a+b) (a - b)2 = a2 - 2ab + b2 = (a-b).(a-b) a2 - b2 = (a + b) . (a – b) vzorce : (a+b)2 ; (a-b)2 ; a2 – b2 (a + b)2 = a2 + 2ab + b2 = (a+b).(a+b) (a - b)2 = a2 - 2ab + b2 = (a-b).(a-b) a2 - b2 = (a + b) . (a – b) vzorce : (a+b)2 ; (a-b)2 ; a2 – b2 (a + b)2 = a2 + 2ab + b2 = (a+b).(a+b) (a - b)2 = a2 - 2ab + b2 = (a-b).(a-b) a2 - b2 = (a + b) . (a – b)